Quality culture, quality work culture, and educational quality: A systematic literature review - Sahdat Sahdat; Muhammad Rizhan; Edi Sulistiawan; Aslamiah Aslamiah; Celia Cinantya (Curricula: Journal of Curriculum Development, 2025)
The pursuit of educational quality is a primary goal for educational institutions. However, sustainable improvement often fails without a strong underlying culture. Understanding the distinction and relationship between 'quality culture' (the shared values) and 'quality work culture' (the enacted behaviors) is crucial, yet the literature often defines these terms ambiguously. This study aims to conceptually map the relationships among quality culture, quality work culture, and their collective impact on educational quality, drawing on existing literature. This research uses a Systematic Literature Review (SLR) methodology. Data were collected by searching major academic databases (e.g., Scopus and Google Scholar) using specific keywords. A total of 2020-2025 articles were selected through a rigorous screening process and synthesized. The findings reveal that 'quality culture' serves as the foundational element, encompassing shared beliefs, values, and commitment to quality. 'Quality work culture' is the practical application of these values, manifesting as consistent processes, behaviors, and continuous improvement practices. The literature confirms a strong, reciprocal relationship: a quality culture enables the development of a quality work culture, and both are significant predictors of sustainable educational quality, thereby affecting teacher performance and student outcomes.    Abstrak Upaya pencapaian mutu pendidikan adalah tujuan utama lembaga pendidikan. Namun, perbaikan berkelanjutan seringkali gagal tanpa landasan budaya yang kuat. Memahami perbedaan dan hubungan antara 'budaya mutu' (nilai-nilai bersama) dan 'budaya kerja mutu' (perilaku yang diterapkan) sangatlah penting, namun seringkali masih ambigu dalam literatur. Penelitian ini bertujuan untuk memetakan secara konseptual hubungan antara budaya mutu, budaya kerja mutu, dan dampaknya secara kolektif terhadap mutu pendidikan berdasarkan literatur yang ada. Penelitian ini menggunakan metodologi Systematic Literature Review (SLR). Data dikumpulkan dengan menelusuri database akademik utama (seperti Scopus dan Google Scholar) menggunakan kata kunci spesifik. Sejumlah artikel yang terbit antara 2020-2025 dipilih melalui proses penyaringan yang ketat dan disintesis. Temuan penelitian mengungkapkan bahwa 'budaya mutu' berfungsi sebagai elemen fundamental, mencakup keyakinan, nilai-nilai, dan komitmen bersama terhadap mutu. 'Budaya kerja mutu' adalah penerapan praktis dari nilai-nilai tersebut, yang terwujud dalam proses, perilaku, dan praktik perbaikan berkelanjutan yang konsisten. Literatur mengkonfirmasi adanya hubungan timbal balik yang kuat: budaya mutu memungkinkan pengembangan budaya kerja mutu, dan keduanya merupakan prediktor signifikan terhadap mutu pendidikan yang berkelanjutan, yang berdampak pada kinerja guru dan hasil belajar murid. Kata Kunci: budaya kerja berkualitas; budaya mutu; mutu pendidikan